Challenges of 4IR implementation in post offices in developing countries: A case study of South Africa (Interdisciplinary Journal of Management Sciences, 2025)
The Fourth Industrial Revolution (4IR) presents an unprecedented opportunity for post offices in developing countries to modernise and enhance their services, addressing the evolving demands of a digital economy. However, implementing 4IR technologies in this sector is fraught with challenges, including inadequate infrastructure, corruption, inclusion bias, disparities in employee skillsets, and financial constraints. This study investigates these challenges, focusing on the South African context, to provide actionable insights and recommendations for effective 4IR adoption. The research adopts a qualitative design, utilising semi-structured interviews with 25 purposively selected participants across five socioeconomic classes in South Africa. This approach ensured the inclusion of diverse perspectives on the risks and barriers associated with 4IR implementation. Data were analysed using thematic analysis to identify key challenges and potential strategies to address them. The findings reveal significant hurdles, including corruption in financial management, insufficient infrastructure to support digital technologies, exclusion of underserved populations, skillset gaps among employees, and limited financial resources. These challenges highlight systemic and structural barriers that hinder the post office's ability to transition into a fully digitalised environment. To address these issues, the study recommends measures such as establishing stringent financial oversight mechanisms, investing in infrastructure upgrades, bridging skillset gaps through training and mentorship programmes, adopting inclusive service models, and fostering equity through community engagement. A strategic and collaborative approach to 4IR implementation can help post offices in developing countries overcome challenges, modernise operations, enhance service delivery, and drive digital transformation and national development.
Keywords: Corruption; developing countries; inclusion bias; Fourth Industrial Revolution; infrastructure; post offices; skillset disparities